LEGAL NATURE OF COERCIVE MEASURES OF A MEDICAL NATURE AND THEIR GOALS - Гайратжон Окмирзаевич Эрматов (Modern American Journals, 2026)
This article sets out the issues of improving the institution of coercive measures of a medical nature and streamlining its legal basis; An analysis of regulatory legal acts in this area is carried out. The grounds for the court to impose coercive measures of a medical nature on a person who committed a dangerous act were also considered; goals, types of these measures; general grounds for their application; the procedure for appointment, extension, amendment and termination; as well as the rules for the application of coercive measures of a medical nature imposed simultaneously with punishment.
Keywords: Sanity, chronic alcoholism, persons suffering from drug addiction or substance abuse, convicts, coercive medical measures.